The sustainability of technology-aided leadership adoption among school leaders: If it could ever be this real forever - Mat Rahimi Yusof; Hapini Awang; Mohd Faiz Mohd Yaakob; Mohd Fairuz Jaafar; Mohd Yusri Ibrahim; Pang Lai Chaw (Institute of Advanced Engineering and Science, 2023)
The 21st century has become a challenging moment for all sectors including education. The rapid advancement of technology has brought a huge impact to leadership style among school leaders in Malaysia. Hence, this quantitative identified the level of technology-aided leadership and analyze the behavioral constructs that contribute to technology-aided leadership. A total of 365 questionnaires adapted from the national educational technology standards for administrators (NETS-A) were answered by respondents. statistical packages for social sciences (SPSS) version 26 and Smart PLS 3 were used to analyze the data. Interestingly, the results revealed that the level of technology-aided leadership is high and the six constructs of technology-aided leadership among principals are valid. The constructs are i) Productivity and professional practice; ii) Teaching and learning; iii) Social, legal, and ethics; iv) Leadership and vision; v) management support and operations; and vi) Assessment and evaluation. In general, school leaders should take the opportunity to develop themselves to become high-tech leaders. Meanwhile, the 31 indicators that are verified in this study can be used to evaluate the behavior of technological leadership. Finally, further research is strongly encouraged to enlarge the scope by collecting the data from all Malaysian states to obtain more accurate and generalizable results.